Association of triglyceride-glucose index, low and high-density lipoprotein cholesterol with all-cause and cardiovascular disease mortality in generally Chinese elderly: a retrospective cohort study - Su, Donghai; An, Zhantian; Chen, Liyuan; Chen, Xuejiao; Wu, Wencan; Cui, Yufang; Cheng, Yulin; Shi, Songhe (Frontiers in Endocrinology, 2024)
Background: The impact of baseline triglyceride-glucose (TyG) index and abnormal low or high-density lipoprotein cholesterol (LDL-C or HDL-C) levels on all-cause and cardiovascular disease (CVD) mortality remains unclear. This study aimed to investigate the relationship between TyG index and LDL-C or HDL-C and all-cause and CVD mortality. Methods: This retrospective cohort study analyzed data from health examinations of 69,068 older adults aged ≥60 in Xinzheng City, Henan Province, China, between January 2013 and January 2023. Cox proportional risk regression models were used to estimate the hazard ratio (HR) and 95% confidence interval (CI) of the TyG index and LDL-C or HDL-C about all-cause and CVD mortality. Restricted cubic spline was used to assess the dose-response relationship. Results: During 400,094 person-years of follow-up (median follow-up 5.8 years, 13,664 deaths were recorded, of which 7,045 were due to CVD. Compared with participants in the second quartile of the TyG index, participants in the fourth quartile had a 16% increased risk of all-cause mortality, and an 8% increased risk of CVD mortality. Similar results were observed in LDL-C and HDL-C, with all-cause and CVD mortality risks for participants in the fourth quartile compared with participants in the third quartile for LDL-C of (HR: 1.07, 95% CI: 1.02,1.12) and (HR: 1.09, 95% CI: 1.01,1.17), respectively. The risk of all-cause and CVD mortality in participants in the fourth quartile group compared with those in the second HDL-C quartile group was (HR: 1.10, 95% CI: 1.05,1.16) and (HR: 1.11, 95% CI: 1.04,1.18), respectively. We found that the TyG index was nonlinearly associated with all-cause and CVD mortality (P non-linear <0.05), and LDL-C was nonlinearly associated with all-cause mortality (P non-linear <0.05) but linearly associated with CVD mortality (P non-linear >0.05). HDL-C, on the other hand, was in contrast to LDL-C, which showed a non-linear association with CVD mortality. We did not observe a significant interaction between TyG index and LDL-C or HDL-C (P >0.05). Conclusion: TyG index and LDL-C or HDL-C increased the risk of all-cause and CVD mortality, especially a high TyG index combined with abnormal LDL-C.